Efficiency of the data generated by the robotic milking system for comprehensive diagnosis of mastitis in cows - M. N. Isakova; M. V. Ryaposova (Ветеринария сегодня)
Early mastitis diagnosis and treatment play a significant role in reducing the disease incidence in a dairy herd. Examination of the animals (n = 61) milked with VMS™ V300 automated voluntary milking system (DeLaval, Sweden) showed that mean milk yield was 15.03 kg (min – 4.50 kg, max – 24.52 kg); mean milking time in the group was 8 min 14 sec (min – 5 min 24 sec, max – 12 min 29 sec) during the observation period equal to 10,300 milkings. Milking time for the majority of the cows (67.2%) complied with the standards and equaled to 4–7 min, mean milking time for 32.7% of the animals was 8 minutes. Mean interval between milkings in the test animal group was 11 hours 30 minutes (min – 6 h 04 min, max – 18 h 54 min). Mean electrical conductivity of the milk was 4.14 1/Om.cm3 for the whole group of animals. Determined mean mastitis detection index (MDi) was 1.6 and varied in the range of 1.03 to 1.41. Minimal and maximal MDi was 1.0 and 11.1, respectively. Diagnostically representative increase in MDi within 1.8–2.2 was observed in 24.6% of animals. Significant MDi increase to more than 2.2 was found in 21.3% of high-yielding cows. All animals with MDi higher than 1.8 (28 animals) were examined for mastitis. Inflammatory reactions in udder were detected in 28.6% of the animals, clinical and latent inflammations were detected in 7.1 and 21.4% of the cows, respectively. Tests of mammary gland secretion showed that average somatic cell count was up to 200 and 201–300 ths cells/mL in 45.9 and 37.7% of the animals, respectively. Udder secretions of 4.9% of cows contained 301–400 ths somatic cells/mL. In 9.8% of tested animals average somatic count was 401–700 ths somatic cells/mL, and in 1.6% of the animals – more than 701 ths somatic cells/mL. Microbiological and PCR tests of mammary gland secretion samples taken from the animals with mastitis detected the following contagious and coliform mastitis agents: Staphylococcus spp. (St. epidermidis, St. saprophyticus, St. haemolyticus), Streptococcus agalactiae, Staphylococcus aureus, Escherichia coli, Enterococcus faecium. Various diagnostic techniques are found to be used for detection of mastitis in the herd and the data generated by robotic voluntary milking station such as mastitis detection index (MDi) can be used for earlier detection of changes in cow’s mammary gland.